Understanding 'context' in realist evaluation and synthesis. Issue 5 (3rd September 2022) - Greenhalgh, Joanne; Manzano, Ana
ABSTRACT: Context is a key concept in developing realist causal explanations but its conceptualisation has received comparatively less attention. We conducted a review to explore how context is conceptualised within realist reviews and evaluations. We purposively selected 40 studies to examine: How is context defined? And how is context operationalised in the findings? We identified two key 'narratives' in the way context was conceptualised: 1) Context as observable features (space, place, people, things) that triggered or blocked the intervention; assuming that context operates at one moment in time and sets in motion a chain reaction of events. 2) Context as the relational and dynamic features that shaped the mechanisms through which the intervention works; assuming that context operates in a dynamic, emergent way over time at multiple different levels of the social system. These two context narratives have different implications for the design, goals and impact of realist reviews and evaluations.